Van Hove singularity in the magnon spectrum of the antiferromagnetic quantum honeycomb lattice - G. Sala (Nature Portfolio, 2021)
Honeycomb lattices with interacting spins can host rich magnetic behaviour; however, typically features are complicated by additional interactions. Here, the authors perform neutron scattering on YbCl3, which exhibits near perfect two-dimensional magnetism, providing a benchmark for other materials.